Kepemimpinan Lembaga Pendidikan Islam di MAN 2 Model Medan - Ade Irvan Margolang; Azwar Alamsyahdana; Jogi Pras; Khairul v; Muharil Ashari; M Rezi Syahbanda Nst; Rizki Akmalia (Departement of Mathematics Education, 2023)
Leadership developed by individuals in leading Islamic educational institutions will have a significant impact on improving the quality of these institutions. Leaders of Islamic educational institutions can use some of the characteristics of Islamic leadership to carry out leadership tasks. Islamic leadership strikes a balance between worldly and spiritual leadership by prioritizing long-term goals over short-term organizational goals, requiring a strong commitment to Islamic principles, and treating leadership responsibilities not only as a human responsibility that is only accountable to members but also to God. SWT. Leadership developed by individuals in leading Islamic educational institutions will have a significant impact on improving the quality of these institutions.